(untitled) (Mongolian Journal of Agricultural Sciences, 2019)
There are many factors that influence the character of bacterial metabolism and enzyme production.For the maximum production of the desired products, the media components and fermentation conditions should be optimized. In our investigation, we improved the amylase production of Bacillus subtilis M4 mutant strain by the combination of two optimization techniques. The cultural conditions (time period, temperature, pH, inoculum volume) and medium ingredients (various carbon, organic and inorganic nitrogen sources, chlorides, sulfates, phosphates, carbonates) were optimized by one factor at a time methodology (OFAT) and response surface methodology (RSM) to increase the amylase production. The optimum conditions for amylase production were found be the following: 35ºC, pH range 7 and incubation time 72h, inoculum volume 8% (v/v). Optimum medium composition for amylase production was the following: starch 12.9 g, peptone 9.75 g, calcium carbonate 0.439 g, magnesium sulfate 0.464 g and potassium chloride 0.464 g per liter. When applied to our optimized medium in the fermentation process, the enzyme activity increased from 0.741 to 1.58 U/ml, which means a 2.1-fold increase compared to the original medium.